A stakeholder-based system dynamics model of return-to-work: a research protocol - Arif Jetha; Glenn Pransky; Jon Fish; Susan Jeffries; Lawrence J. Hettinger (SAGE Publishing, 2015)
Background. Returning to work following a job-related injury or illness can be a complex process, influenced by a range of interrelated personal, psychosocial, and organizational components. System dynamics modelling (SDM) takes a sociotechnical systems perspective to view return-to-work (RTW) as a system made up of multiple feedback relationships between influential components. Design and Methods. To build the RTW SDM, a mixed-method approach will be used. The first stage, that has already been completed, involved creating a baseline model using key informant interviews. Second, in two manufacturing companies, stakeholder-based models will be developed through interviews and focus groups with senior management, frontline workers, and frontline supervisors. Participants will be asked about the RTW process in general and more targeted questions regarding influential components. Participants will also be led through a reference mode exercise where they will be asked to estimate the direction, shape and magnitude of relationships between influential components. Data will be entered into the software program Vensim that provides a platform for visualizing system-structure and simulating the effects of adapting components. Finally, preliminary model validity testing will be conducted to provide insights on model generalizability and sensitivity. Expected Impact of the study for Public Health. The proposed methodology will create a SDM of the RTW process using feedback relationships of influential components. It will also provide an important simulation tool to understand system behaviour that underlies complex RTW cases, and examine anticipated and unanticipated consequences of disability management policies.